2020
DOI: 10.5114/jcb.2020.98117
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of computed tomography- and magnetic resonance imaging-based target delineation for cervical cancer brachytherapy

Abstract: Purpose The objective of this study was to compare and assess the accuracy of computed tomography (CT)-based target delineation with that of magnetic resonance imaging (MRI)-based on high-dose-rate brachytherapy (HDR-BT) for patients with cervical cancer. Material and methods Data of 20 patients with locally advanced cervical cancer were collected and evaluated. Dimensions, conformity, and dose parameters of high-risk clinical target volume (CTV HR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…More consistent and well-curated training data using MRI will eventually lead to a better segmentation performance of DL-based CTV segmentation. Wang et al 39 demonstrated that CT scan cannot clearly distinguish between structures of residual GTV, cervix, uterus, and vagina. Also, CT provides a poor definition of parametrial tumor infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…More consistent and well-curated training data using MRI will eventually lead to a better segmentation performance of DL-based CTV segmentation. Wang et al 39 demonstrated that CT scan cannot clearly distinguish between structures of residual GTV, cervix, uterus, and vagina. Also, CT provides a poor definition of parametrial tumor infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…The American Brachytherapy Society (ABS) conducted a survey of image guided cervical brachytherapy practices in the United States, 95% of participants always use CT, and 34% always use MRI for dose specification to target (79). However, CT-based target contouring is not recommended because in CT images the target is overestimated in size in comparison to the target from MRI images (80).…”
Section: D-based Brachytherapymentioning
confidence: 99%
“…The American Brachytherapy Society (ABS) conducted a survey of image guided cervical brachytherapy practices in the United States, 95% of participants always use CT, and 34% always use MRI for dose specification to target (79). However, CT-based target contouring is not recommended because in CT images the target is overestimated in size in comparison to the target from MRI images (80).…”
Section: D-based Brachytherapymentioning
confidence: 99%